DNA methylation markers for cancer risk prediction of vulvar intraepithelial neoplasia. Issue 10 (19th January 2021) - Thuijs, Nikki B.; Berkhof, Johannes; Özer, Müjde; Duin, Sylvia; van Splunter, Annina P.; Snoek, Barbara C.; Heideman, Daniëlle A. M.; van Beurden, Marc; Steenbergen, Renske D. M.; Bleeker, Maaike C. G.
Abstract: Current clinical and histological classifications are unable to determine the risk of vulvar squamous cell carcinoma (VSCC) in high‐grade vulvar intraepithelial neoplasia (VIN), making prognostic biomarkers highly needed. We studied host‐cell DNA methylation markers in high‐grade squamous intraepithelial lesion (HSIL) and differentiated VIN (dVIN) without VSCC, in HSIL and dVIN adjacent to VSCC and in human papillomavirus (HPV) positive and negative VSCC, relative to control vulvar tissues. A series of 192 formalin‐fixed paraffin‐embedded vulvar samples, including VSCC (n = 58), VIN adjacent to VSCC (n = 30), VIN without VSCC during follow‐up (n = 41) and normal vulvar tissues (n = 63), were tested for 12 DNA methylation markers with quantitative multiplex methylation‐specific PCR (qMSP). HPV status was determined by p16 INK4A immunohistochemistry and high‐risk HPV PCR analysis. Logistic regression analyses were used to determine methylation patterns and methylation marker performance for VIN and VSCC detection. Methylation markers showed significantly higher methylation levels with increasing severity of disease. VIN adjacent to VSCC showed a similar methylation‐high pattern as VSCC, while VIN without VSCC displayed a heterogeneous methylation pattern. Vulvar carcinogenesis is associated with increased DNA methylation. Higher DNA methylation levels in VIN seem to reflect higher cancer risk, emphasizing the high potential of DNA methylation biomarkers in the diagnostic workup of VIN. As a next step, longitudinal studies are needed to verify the prognostic value of methylation biomarkers as a clinical tool for stratification of cancer risk in women with VIN. Abstract : What's new? In high‐grade vulvar intra‐epithelial neoplasia (VIN), existing clinicopathological classifications lack accuracy in predicting cancer risk, resulting in a need for objective prognostic biomarkers. Here, 12 DNA methylation markers were investigated for prognostic capability in a series of high‐grade squamous intraepithelial lesion, differentiated VIN, and vulvar carcinomas. For all 12 methylation markers, as disease severity increased, methylation levels also increased. Methylation patterns were more heterogeneous for VIN without vulvar squamous cell carcinoma. The results link elevated DNA methylation levels with increased VIN cancer risk and indicate that methylation biomarkers are promising diagnostic tools for cancer risk stratification in VIN.